(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The word “computer”, originally, referred to a person in charge of performing calculations. At the end of the 19th century, the Civil Service of the United States recruited officials to carry out computer tasks. Today, the situation seems to have reversed: the administrations around the world are recruiting computers that are increasingly capable of carrying out many of the tasks of public officials.The Council of State judgment no. 8472/2019 recently widened the range of the principles concerning the use of algorithms in the administrative activity set forth by previous jurisprudence, opening up to the issue of compliance with the European legal framework on personal data protection. It is necessary to claim the right to doubt of machine decisions, whose origins are “algorithmic, all too algorithmic".